A retrospective multicenter study of quantitative bone SPECT/CT to predict the surgical removal of the accessory navicular bone. Issue 9 (16th April 2021) - Kim, Ji-Young; Kim, Ji Young; Park, Soo Bin; Kim, Chulhan; Lee, Won Woo
Abstract : Objective: The maximum standardized uptake value (SUVmax) in single-photon emission computed tomography/computed tomography (SPECT/CT) can help quantify disease activity of the accessory navicular bone (ANB). In this multicenter quantitative bone SPECT/CT study, we investigated whether SUVmax was correlated with ANB severity, thereby allowing prediction of surgical resection for ANB treatment. Methods: Two-hundred forty-six patients (men:women = 135:111, mean age = 39.3 years), who had undergone quantitative Tc-99m diphosphonate SPECT/CT of the feet, were recruited from four hospitals. SUVmax was measured using vendor-provided quantitation software. The SUVmax values were compared in relation to ANB type (type 1 = 62, type 2 = 136 and type 3 = 14), presence of pain and surgical treatment. Results: SUVmax (mean ± SD) was the highest in type 2 ANB (4.41 ± 5.2; P = 0.0101). The 17 resected ANBs showed greater SUVmax (8.27 ± 5.23; P < 0.0001) than the 141 asymptomatic ANBs (2.30 ± 1.68) or the 54 symptomatic ANBs without surgery (6.15 ± 4.40). Since surgery is exclusively indicated for ANB type 2, surgical resection was investigated only in these cases. In univariate analysis, young age and SUVmax were significantly associated with surgical treatment, but only SUVmax was a significant predictor of surgery in multivariate analysis ( P < 0.0001). Type 2 ANBs were treated by surgery in 32.5% (13/40) of the cases when SUVmax was ≥5, and in only 1.35% (1/74) of the cases when SUVmax was <5 ( P < 0.0001). Conclusion: ANB disease activity and excision were strongly associated with the SUVmax derived from quantitative bone SPECT/CT. Our study suggests an absolute SUVmax cutoff for ultimate ANB surgical treatment, but additional prospective studies are required to validate this finding.